Developing Tri Hita Karana based Student Worksheet to Improve Primary School Students' Critical Thinking During Learning from Home - Winaya, I Made Astra (Media Komunikasi FPIPS, 2021)
This study aimed at developing Tri Hita Karana based student worksheets to improve students' critical thinking skills. The model used in the development of Tri Hita Karana-based worksheets in this study was the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The results of this study revealed that the validity of the developed student worksheets was excellent. It was indicated by the average test scores of material and design experts which was about 83.75% and 81.58% and considered having very good quality. The readability test in class A and B obtained an average score of 82.27% and 80.64% with very good quality. The results also showed that the developed worksheets were able to improve students' critical thinking skills. This could be seen from the n-gain values in class A and B of 0.74 and 0.78 in the medium category, and the sig value. in the paired sample t test of 0.00 in both classes. Teachers and students gave good responses to the developed worksheets. In conclusion, Tri Hita Karana based student worksheets with the feasibility and effectiveness in improving students' critical thinking skills were successsfully developed.